2020
DOI: 10.3390/ijms21144816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis, Structural Insights, and Substrate/Drug Interaction of CYP128A1 in Mycobacterium tuberculosis

Abstract: Cytochrome P450 monooxygenases (CYPs/P450s) are well known for their role in organisms’ primary and secondary metabolism. Among 20 P450s of the tuberculosis-causing Mycobacterium tuberculosis H37Rv, CYP128A1 is particularly important owing to its involvement in synthesizing electron transport molecules such as menaquinone-9 (MK9). This study employs different in silico approaches to understand CYP128 P450 family’s distribution and structural aspects. Genome data-mining of 4250 mycobacterial species has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Recent studies from our laboratory focusing on bacterial species revealed that the lifestyle of an organism plays a key role in shaping P450 content vis à vis P450s helping microbes to adapt to ecological niches. However, these studies were limited to few groups of bacterial species belonging to the genera Streptomyces [ 49 , 50 ] and Mycobacterium [ 51 , 52 , 53 ] and from the phyla Cyanobacteria [ 54 ] and Firmicutes [ 55 , 56 ]. Furthermore, to date, a comparative analysis of P450s in the Gammaproteobacterial species has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from our laboratory focusing on bacterial species revealed that the lifestyle of an organism plays a key role in shaping P450 content vis à vis P450s helping microbes to adapt to ecological niches. However, these studies were limited to few groups of bacterial species belonging to the genera Streptomyces [ 49 , 50 ] and Mycobacterium [ 51 , 52 , 53 ] and from the phyla Cyanobacteria [ 54 ] and Firmicutes [ 55 , 56 ]. Furthermore, to date, a comparative analysis of P450s in the Gammaproteobacterial species has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A point to be noted is that, among bacterial species, species belonging to the phylum Actinobacteria have the highest average number of P450s ( Table 1 ). This indicates selective enrichment of P450s in these species due to their adaptation to ecological niches vis a vis P450s, helping them adapt to diverse ecological niches described elsewhere [ 58 , 74 , 75 ]. Salinispora species P450s, along with P450-fragments, are presented in Table S2 .…”
Section: Resultsmentioning
confidence: 57%
“…If a P450 family is conserved or few P450 families are co-presence, these families play an important role in a species’s primary- or secondary-metabolism. Previous studies showed that this type of P450s prominently plays a role in secondary metabolism, helping species adapt to diverse ecological niches [ 58 , 59 , 72 , 74 , 75 ]. The importance of P450 families that are conserved and co-presence in Salinispora species is discussed in detail in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon of grouping P450s from species with similar life style/adaption to similar ecological niches was observed in some bacterial [35][36][37] and fungal species [38][39][40]. This indicates that after speciation, lifestyle/ecological niches played a key role in changing/preserving the amino acid content, as observed for different P450s families in bacteria [35][36][37] and fungi [38][39][40]. 1).…”
Section: Cyp51s Grouped As Per Tremellomycetes Lifestylementioning
confidence: 60%